2014
DOI: 10.1371/journal.pone.0085127
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Fire Severity Patterns in Topographic, Convective and Wind-Driven Historical Wildfires of Mediterranean Pine Forests

Abstract: Crown fires associated with extreme fire severity are extremely difficult to control. We have assessed fire severity using differenced Normalized Burn Ratio (dNBR) from Landsat imagery in 15 historical wildfires of Pinus halepensis Mill. We have considered a wide range of innovative topographic, fuel and fire behavior variables with the purposes of (1) determining the variables that influence fire severity patterns among fires (considering the 15 wildfires together) and (2) ascertaining whether different varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 61 publications
3
60
0
2
Order By: Relevance
“…These findings were found acceptable as the fire occurrences would not only depend on the PW but also other factors, e.g., temperature, precipitation, wind regimes, topography, fuel types, source of ignitions, etc. [8,26,[61][62][63]. In addition, we observed that other input variables of the FFDFS (i.e., TS, NMDI, and NDVI) demonstrated similar results (i.e., 50.60%, 65.50%, and 61.95% of the fire spots fell under the "high danger" category for TS, NMDI, and NDVI respectively during 2009-2011).…”
Section: Evaluation Of the Impact Of Daily Pw On The Fire Danger Condmentioning
confidence: 51%
“…These findings were found acceptable as the fire occurrences would not only depend on the PW but also other factors, e.g., temperature, precipitation, wind regimes, topography, fuel types, source of ignitions, etc. [8,26,[61][62][63]. In addition, we observed that other input variables of the FFDFS (i.e., TS, NMDI, and NDVI) demonstrated similar results (i.e., 50.60%, 65.50%, and 61.95% of the fire spots fell under the "high danger" category for TS, NMDI, and NDVI respectively during 2009-2011).…”
Section: Evaluation Of the Impact Of Daily Pw On The Fire Danger Condmentioning
confidence: 51%
“…However, the cause of this non-stationary effect of red pine trees on burn severity is unclear. In the literature, numerous variables are involved in determining the burn severity at certain locations during fire events, such as meteorological conditions [21,22], pre-fire forest structure [19,28,31], fuel type and characteristics [25,26] and topography [21,22]. On a broader level, the presence of non-stationary effects of red pine trees on burn severity is due to the dynamics and complexity of the interactions of these relevant variables.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the degree of burn severity is largely determined by various environmental factors, including meteorological conditions [20][21][22], pre-fire forest vegetation type [19,23,24], fuel moisture [25,26], tree stand density [27,28], composition and configuration of pre-fire forest [19,[29][30][31][32][33], tree characteristics [34], and topography [19][20][21][22][23][24]28,30,33], as well as the interactions among relevant variables [22,24]. Considering that meteorological conditions and topological characteristics are not manageable factors, controlling susceptible fuels might be the only practical tool for lowering burn severity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fire agencies invested heavily in suppression resources and improved remarkably their training and fire behavior knowledge. MWFs were classified into three different fire spread patterns: topography-driven fires, wind-driven fires and convective fires (Lecina-Diaz et al 2014, Duane et al 2015. Lázaro et al (2014) and Lázaro-Palacios et al (2016) made a characterization of fire typologies in this region based on synoptic weather condition analysis across the study area.…”
Section: Main Wildland Fires and Fire Typologiesmentioning
confidence: 99%
“…Depending on the spread scheme, fires have been usually classified into three different fire spread patterns according to the dominant spread factor: topography (topography-driven fires), wind (wind-driven fires) or fuel accumulation that could be related to convective fires (Lecina-Diaz et al 2014, Duane et al 2015. Topography-driven fires are characterized by local convective winds caused by differential solar heating of the land surface.…”
Section: Introductionmentioning
confidence: 99%